Tom Hansen’s Defense Mechanisms in (500) Days of Summer Movie by Marc Webb - Arumira Yusuf; Rifka Pratama (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
The writer intends to analyze one of the remarkable movies directed by Marc Webb which is titled (500) Days of Summer in this thesis. This thesis is written in a purpose to analyze acts of defense mechanisms portrayed in the main character of the film, Tom Hansen, as well as to analyze several intrinsic elements of the film including characterization and conflict. The writer utilizes psychological and objective approaches in order to analyze Tom Hansen’s existing defense mechanism and the intrinsic elements in the film. Meanwhile, library research is used as the method of research in collecting the data for this thesis. Finally, the result of the data analysis shows that there are several acts of defense mechanisms represented by Tom Hansen character to struggle with his love for Summer Finn such as projection, denial, displacement, reaction formation, and sublimation that differ in how they operate to undergo Tom Hansen’s negative effects.Keywords: (500) Days of Summer; Marc Webb; Tom Hansen; Defense Mechanisms; Movie.